CPA Examination: Accounting Practice. - Chamberlain, John H. (The Accounting Review, 1967)
Abstract This article presents several questions and answers that were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (CPA) and were presented as the first half of the CPA examination in accounting practice on November 2, 1966. The candidates were required to solve all problems. In one of the questions,the president of Eastern Co. wants guidance on the advisability of eliminating product C, one of the company's three similar products, or investing in new machinery to reduce the cost of product C in the hope of reversing product Cs operating loss sustained in 1966. The three similar products are manufactured in a single plant in about the same amount of floor space and the markets in which they are sold are very competitive. It is required to prepare a schedule showing the contribution of product C to the recovery of fixed costs and expenses for the year ended October 31, 1966. Assume that each element of cost and expense is entirely fixed or variable within the relevant range and that the change in inventory levels has been negligible.